Arch-spring or windlass mechanism? The stiffness of sprinters` and swimmers` feet: A pilot study - Goldmann, J. P.; Grothe, S.; Kersting, U. (28th Annual Congress of the European College of Sport Science, 4-7 July 2023, Paris, France, 2023)
INTRODUCTION: The human foot is thought to function like a flexible spring (Ker 1987) or a stiff lever (Hicks 1954). In both mechanisms, the stiffness of the plantar aponeurosis (PA) plays a central role in the deformation of the longitudinal arch (LA) under loading. If the PA is sufficiently stiff, metatarsophalangeal joint (MPJ) dorsiflexion should be closely coupled to LA deformation. We assume that, due to their daily impact load, sprinters have stiffer LA than swimmers. Therefore, more force might be needed for MPJ dorsiflexion, which should lead to greater deformation of the LA of sprinters compared to swimmers.